Palonosetron versus ondansetron for prevention of nausea and vomiting after total abdominal hysterectomy under spinal anesthesia with intrathecal morphine: a double-blind, randomized controlled trial - Campos, Guilherme Oliveira; Martins, Marcelo de Jesus [UNESP]; Jesus, Gabriel Nascimento; Rios de Oliveira, Paulo Roberto; Lessa, Caio Nogueira; Macedo Fernandes de Oliveira Junior, Joao Carlos; Santana de Castro Alves, Lucas Jorge; Alves, Rodrigo Leal; Pinheiro Modolo, Norma Sueli [UNESP] (Bmc, 2019)
Background Hysterectomy is a widely performed surgery and neuraxial anesthesia with intrathecal morphine provides superior quality of recovery. Postoperative nausea and vomiting (PONV) is a frequent problem with intrathecal morphine use. Although palonosetron is effective for prevention of PONV after general anesthesia, its efficacy after neuraxial anesthesia has not been established. This study was conducted to compare the use of palonosetron with ondansetron for PONV prophylaxis in patients at a high risk of PONV during total abdominal hysterectomy (TAH) under spinal anesthesia with intrathecal morphine. Methods This prospective, randomized double-blind study conducted at Sao Rafael Hospital involved 140 American Society of Anesthesiologists physical status I or II women who underwent TAH under spinal anesthesia with intrathecal morphine and who had at least 3 risk factors for PONV based on Apfel's simplified score. The patients were randomized into two groups: one received palonosetron whereas the other received ondansetron. All patients received spinal anesthesia with intrathecal morphine, as well as dexamethasone plus palonosetron or ondansetron for PONV prophylaxis. The overall incidence of PONV, incidence of early- and late-onset nausea and vomiting, severity of nausea, and use of rescue antiemetics were recorded. Results The overall incidence of PONV was 42.9% in the palonosetron group and 52.9% in the ondansetron group (p > 0.05). No significant differences existed in the incidence of early- and late-onset nausea or early-onset vomiting between the two groups. The incidence of late-onset vomiting was significantly lower in the palonosetron group. Conclusions Palonosetron exhibited efficacy similar to that of ondansetron for reducing the overall incidence of PONV after TAH under spinal anesthesia with intrathecal morphine; however, palonosetron reduced the incidence of late-onset vomiting significantly better than ondansetron.
Keywords: Antiemetics; Morphine; Ondansetron; Postoperative nausea and vomiting; Spinal anesthesia